PERAN GURU MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DALAM MEMBENTUK AKHLAK PESERTA DIDIK SMPN 2 TELUKJAMBE TIMUR - Siti Awalia Kurniasari; Ainur Alam Budi Utomo; Agus Fudholi (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
This research was conducted because based on the results of observations it was found that many students could not apply morals properly at school. It aims to find out the role and strategy of Islamic religious education and ethics subject teachers in shaping the morals of students at SMPN 2 Telukjambe Timur. This research method uses a qualitative research approach with a case study approach. The subjects of this research used Islamic religious education and character education subject teachers and 9 students. The research analysis begins with collecting data, reducing data, presenting data to drawing conclusions. the series is presented in a description so that it is easy for readers to understand The results of the study state that students experience moral changes because there is external encouragement through Islamic religious education and character education teachers. In addition, school programmes and a good learning environment can encourage students to learn to become better individuals.